Structural, morphological and opto-nonlinear studies of Cu:NiO: glass thin films facilely designed by spin coater for electro-optics. (22nd May 2019) - Ganesh, V; Shkir, Mohd; Anis, Mohd; AlFaify, S
Abstract: Fabrications of pure and Cu (1, 5, 10 and 15 wt%) doped NiO (Cu–NiO) films was attained using spin-coating deposition technique onto the glass substrates. Influences of Cu on pure NiO were studied regarding structure, morphological, linear and nonlinear optical traits by XRD, EDXs, AFM, UV–vis-NIR, Z-scan, respectively. XRD studies confirm the single phase of Cu doped NiO and EDX mapping confirms the interaction Cu atoms with pure NiO matrix. AFM studies confirm the formation spherical shaped nanostructures after addition of Cu this nanostructure formation increased with increased size. The transmittance, reflectance and absorption of all the samples were showing the same movement with decreasing band gap from 3.87 to 3.80 eV. Various nonlinear constants were estimated from Z-scan studies. The values noticed for χ 1, χ 2, χ 3, and n 2 were in range of 7.5 to 0.5, 8.0 × 10 −8 to 0.5 × 10 −8 esu and 0.5 × 10 −8 to 8.5 × 10 −8 esu, respectively. Moreover, the values of n 2 and β are varying between 8.36 × 10 −9 to 1.18 × 10 −9 cm 2 W −1 and 9.01 to 9.81 for all films.